Melayu Islam dan Batak Kristen: Labelisasi Keagamaan Terhadap Identitas Kesukuan di Sumatera Timur pada Awal Abad Ke-20 - Anwar, Syaiful (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
This article discusses the religious labelling of ethnicity on Malay and Batak identities in East Sumatra in the early 20th century. The labelling refers to the mention of Malay as Islam and Batak as Christian. The labelling of religious identity strengthened along with the start of Dutch East Indies colonization of East Sumatra. The colonization of the Dutch East Indies changed various religious social lives between the inland people who were often called the Bataks with the coastal people called the Malays. Significant changes to the labelling have occurred since the arrival of European zending to the North Tapanuli region and influenced the social life of the Batak people in the inland at the end of the 19th century. Meanwhile, the Malay identity as Islam has become an inseparable unit, even before the colonization of East Sumatra. This article uses the historical method. Heuristics or collection of sources for this article are primary and secondary sources that discuss social situations in the contemporaries. Furthermore, source criticism and interpretation of historical facts will be carried out using theories or concept from the social sciences. the results of the study show that the religious labelling of Malay and Batak identities has two different poles. Malay as an Islamic identity that occurs because of labelling carried out internally. The Malay community identifies itself as Islam which means that Malay is the same as Islam. Meanwhile, Batak identity as a Christian is more likely to emerge due to external consequences. The attitude of the Dutch East Indies colonial politics that wanted to orbit Batak culture has formed various institutions that are mostly filled by zending parties. Therefore, the Batak identity as a Christian is more likely to be carried out by people outside the Christian religion, even though the person who does it is a Batak ethnic but having Islam as his/her religion.